Water used to be infinite: a Brazilian tale of climate change. Issue 1 (14th January 2019) - Santos, Joaquim Rocha dos; Franco, Eduardo Ferreira; Carvalho, Hamilton Coimbra; Armenia, Stefano; Pompei, Alessandro; Medaglia, Carlo Maria
Abstract : Purpose: The purpose of this study is to analyze the impacts of different policies to address the water supply crisis experienced by the metropolitan region of Sao Paulo during 2013 to 2015 and evaluate the resilience of its water supply system for the coming years. Design/methodology/approach: The methodology used in this study is based on the system dynamics simulation paradigm, combined with empirical data obtained from the regional water authority. Findings: The results from the simulations suggest that the first layer of sustainability of the water supply in the region strongly depends on how the system's operator responds to crises, in particular how it balances policies acting on the supply and demand for the resource. Practical implications: Severe water crises typically make salient the perception that water is a finite and public resource. Long-term, sustainable management of the system requires a paradigm shift from widespread, old-fashioned beliefs that water is an infinite resource. It also requires active management to increase the system's preparedness to withstand events caused by climate change. Originality/value: This study contributes to the system dynamics and water resource management literature by presenting an integrative model to evaluate the resilience of a particular water supply system. Although there are previous studies on this subject, the present one focuses on the role that the water authority plays in a crisis and especially on a specific combination of policies to address an episode of crisis in a system unprepared for it.